The interaction of family and educational institutions in the socialization in childhood (Pedagogy of Higher and Secondary Education, 2013)
Rogal’skaya I. P. The interaction of family and educational institutions in the socialization in childhood.The article refers to the coverage features family interaction and educational institutions in the socialization of a child by its specificity in modern conditions of social instability, particularly through the study of pre-school institutions of an open social and educational system that comprehensively linked to the environment.
Keywords: socialization; family; pre-school; interaction; institutions; society